Dissemination through trusted credible messengers: 133 weeks of the Flint Community Webinar on COVID-19 - Heatherlun Uphold; E. Yvonne Lewis; Amy Drahota; Blair Warren; Jennifer Edwards-Johnson; Mary Katherine Crawford; Richard Sadler; Susan J. Woolford; Roni Ellington; Marc Zimmerman; Alison Grodzinski; C. Debra Furr-Holden (Implementation Research and Practice)
Background Community access to evidence-based information is critical, especially during a pandemic, as it can impact knowledge and adoption of health behaviors that affect health disparities. The field of dissemination and implementation (D&I) science is ideally positioned to address this need through its focus on reducing the research-to-practice gap through improved distribution of information. The purpose of this paper is to describe the creation of a weekly webinar series about COVID-19 directed toward community members, and the extent to which webinars were found useful and increased awareness of evidence-based information and services. Lessons learned about this dissemination strategy as well as the selection and involvement of trusted credible messengers (TCMs) to share information are discussed. Method Data were derived from Zoom attendance reports, YouTube views, and survey responses collected about the weekly webinar series over 133 weeks from March 20, 2020 through September 30, 2022. Results The webinar reached a minimum of 877 unique within-webinar participants, representing more than 9,190 in-webinar participant hours and an additional 17,303 YouTube views. A consistent base of weekly attendees (e.g., service providers, community members) reported increasing levels of satisfaction and utility over time. Conclusions This study supports the use of a community webinar series to disseminate evidence-based, locally relevant information through TCMs to improve community access to knowledge of health information and resource utility.